2015
DOI: 10.1039/c5ee01799h
|View full text |Cite
|
Sign up to set email alerts
|

Power generation from chemically cleaned coals: do environmental benefits of firing cleaner coal outweigh environmental burden of cleaning?

Abstract: Power generation from high-ash coals is a niche technology for power generation, but coal cleaning is deemed necessary to avoid problems associated with low combustion efficiencies and to minimize environmental burdens associated with emissions of pollutants originating from ash. Here, chemical beneficiation of coals using acid and alkali-acid leaching procedures is evaluated as a potential coal cleaning technology employing life cycle assessment (LCA). Taking into account the environmental benefits from firin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The mechanism of adsorption complex silica to the following possible reactions during leaching process as shown below. Where a, b, c and x, y, z accordingly in equations (6), (8) and (9) are the stoichiometric coefficient among different element while R is the hydrocarbon groups in coal matrix. DM-Demineralization, DS-Desulfurization, T-Temperature (°C), P-Pressure, t-Time, µm-Micrometer Figure 2.…”
Section: Alkali Leachingmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of adsorption complex silica to the following possible reactions during leaching process as shown below. Where a, b, c and x, y, z accordingly in equations (6), (8) and (9) are the stoichiometric coefficient among different element while R is the hydrocarbon groups in coal matrix. DM-Demineralization, DS-Desulfurization, T-Temperature (°C), P-Pressure, t-Time, µm-Micrometer Figure 2.…”
Section: Alkali Leachingmentioning
confidence: 99%
“…The several literature studies revealed the great potential for chemical cleaning of coals, with better ash removal was obtained from the coal. Chemical cleaning method has not widely employed on a commercial scale due to huge cost related to the requirements of chemicals and the need for dewatering of the post-demineralization and regeneration of reagents from spent solution [8][9][10]. It can be seen from literature only a few studies about the regeneration of chemical reagents from the spent solution by adding a suitable chemical reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Different from in situ gasification where syngas is produced from controlled combustion of coal [8] or ex situ gasification which is generally performed at temperatures higher than 800 o C [9], biogasification can be conducted under mild environmental conditions. In addition, coal does not need to be cleaned before biogasification like those prepared for power generation [10]. This technology can be used for both in situ (abandoned or unmineable coal seams) and ex situ (coal wastes or mined out coal) scenarios [11].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical leaching process usually achieved remove all types of minerals from the coal compared to physical treatment method. Although, chemical cleaning method has not been widely employed on a commercial scale due to huge cost related to the requirement of chemical and need for dewatering and regeneration of reagents from spent solution (Wu and Steel 2007;Waugh and Bowling 1984;Ryberg et al 2015;Sriramoju et al 2017).…”
Section: Introductionmentioning
confidence: 99%